Development of Peanut Quality Criteria for Determination of its Rational Use - Lehnert, S.; Khomenko, O.; Dubinina, A.; Malyuk, L.; Skyrda, O.; Radchenko, A. (Наука та інновації, 2019)
Introduction. The world industrial producers cultivate the four main varieties of peanuts (Spanish, Valencia, Virginia, and
Runner), which have different types and subspecies, whose names may vary in some countries. These varieties differ in
structure, chemical composition, nutritional and biological value, as well as in the areas of industrial use.
Problem Statement. At present, there is no scientific approach to the rational use of peanuts in specific technologies of
food industry, which would take into account its varietal properties and chemical composition. The development of such a
technique will significantly reduce the loss of raw materials, improve the quality of peanut processing products, and increase
the efficiency of production.
Purpose. To make a cluster analysis to find ways for rational use of peanut varieties adapted for cultivation in Ukraine and
to develop appropriate recommendations for the food industry.
Materials and Methods. Nineteen varieties of peanuts have been used in the collection of the Institute of Oilseeds of
the NAAS of Ukraine (Zaporizhzhіa). The cluster analysis method has been used to process the research results and to
classify the peanut varieties.
Results. Peanut quality criteria have been developed for choosing an optimal usage (protein content and its biological
value, lipid and oleic acid content, oxalate index, and content of contaminants). Depending on the usage, the peanut va rieties
have been classified into the three groups: for manufacturing peanut oil, for processing into peanut paste, and for
manufacturing halva, chocolates, cakes, and snack products. The recommendations allow different manufacturers to choose
an optimal usage and to use peanuts for producing high quality products in a more efficient way.
Conclusions. The developed quality criteria can be used as basis for the definition and development of the principles of
rational use of peanuts given their specific properties and are useful for technologists, commodity researchers, breeders,
geneticists, pharmacologists, physicians, and so on. The rational use of peanut varieties will contribute to the manufacture
of competitive high-quality products and increase the profitability of enterprises. Вступ. У світовому промисловому виробництві культивують чотири основні сортотипи арахісу — ’Спеніш’, ’Валенсія’, ’Вірджинія’ та ’Раннер’, які мають різні типи та підвиди, назви яких в деяких країнах можуть варіювати. Ці
сортотипи різняться будовою, хімічним складом, харчовою та біологічною цінністю, а також напрямами промислового використання.
Проблематика. На сьогодні відсутній науковий підхід щодо раціонального використання арахісу в конкретних
технологіях харчової промисловості, який враховував би його сортові властивості й специфічність хімічного складу.
Розробка методики дозволить значно знизити втрати сировини, покращити якість продуктів переробки арахісу та
збільшити ефективність виробництва.
Мета. Використання кластерного аналізу для пошуку шляхів раціонального використання сортів арахісу, адаптованих до вирощування в Україні, та розробка відповідних рекомендацій для харчової промисловості.
Матеріали й методи. Використано 19 сортів арахісу колекції Інституту олійних культур УААН (Запоріжжя). Для
обробки результатів досліджень та розподілу сортів арахісу застосовано метод кластерного аналізу.
Результати. Розроблено критерії якості арахісу для вибору напряму використання (вміст протеїну та його біологічна цінність, вміст ліпідів та олеїнової кислоти, оксалатний індекс, вміст контамінантів). Застосування їх дозволяє
розподіляти сорти арахісу на три групи: для виробництва олії, для переробки в арахісову пасту, для халви, цукерок,
тортів та снекової продукції. Розроблені рекомендації дозволяють підприємствам різного спрямування більш раціонально обирати та використовувати арахіс для отримання продукції високої якості.
Висновки. Розроблені критерії якості є базисом для визначення та розробки принципів раціонального використання арахісу відповідно до його специфічних властивостей та можуть слугувати технологам, товарознавцям, селекціонерам, генетикам, фармакологам, медикам. Раціональне використання сортів арахісу сприятиме виробництву
конкурентоздатних продуктів високої якості та підвищенню рентабельності підприємства. Введение. В мировом промышленном производстве культивируют четыре основных сортотипа арахиса — ’Спениш’, ’Валенсия’, ’Вирджиния’ и ’Раннер’, которые имеют различные типы и подвиды, названия которых в разных
странах могут варьироваться. Эти сортотипы отличаются строением, химическим составом, пищевой и биологической ценностями, а также направлениями промышленного использования.
Проблематика. Сегодня отсутствует научный подход относительно рационального использования арахиса в конкретных технологиях пищевой промышленности, который учитывал бы его сортовые свойства и специфичность химического состава. Разработка методики позволит значительно снизить потери сырья, улучшить качество продуктов
переработки арахиса и повысит эффективность производства.
Цель. Использование кластерного анализа для поиска путей рационального использования сортов арахиса,
адаптированных для выращивания в Украине, и разработка соответствующих рекомендаций для пищевой промышленности.
Материалы и методы. Использовано 19 сортов арахиса коллекции Института масличных культур УААН (г. Запорожье). Для обработки результатов исследований и распределения сортов арахиса использовали метод кластерного анализа.
Результаты. Разработаны критерии качества арахиса для выбора направления использования (содержание протеина и его биологическая ценность, содержание липидов и олеиновой кислоты, оксалатный индекс, содержание
контаминантов). Применение их позволяет распределять сорта арахиса на три группы: для производства масла, для
переработки в арахисовую пасту, для халвы, конфет, тортов и снековой продукции. Разработанные рекомендации
позволяют предприятиям различной направленности более рационально выбирать и использовать арахис для получения продукции высокого качества.
Выводы. Разработанные критерии качества являются базисом для определения и разработки принципов рационального использования арахиса в согласовании с его специфичными свойствами и могут служить технологам, товароведам, селекционерам, генетикам, фармакологам, медикам. Рациональное использование арахиса способствует
производству конкурентоспособных продуктов высокого качества и повышению рентабельности предприятия.